2019
DOI: 10.52859/jba.v6i2.59
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Standar Gri Dalam Laporan Keberlanjutan Di Indonesia: Sebuah Evaluasi

Abstract: This study aims to investigate the level of conformity of economic, social, and environmental information on sustainability report in Indonesia as per GRI G4 guidelines. Content analysis has been applied to a sample of 29 companies listed in the Indonesia Stock Exchange. Conformity and disclosure quality were analyzed descriptively using a specific scoring system for each dimensions. The findings of this research show that the level of conformity of GRI indicators in Indonesia is quite low at 18,9%. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
3
0
7
Order By: Relevance
“…Laporan ini dipandang sebagai upaya perusahaan untuk menyampaikan aktivitas perusahaan yang berkenaan dengan aspek ekonomi, lingkungan dan sosial perusahaan. Tidak hanya itu, laporan keberlanjutan juga membantu perusahaan untuk menetapkan tujuan perusahaan, mengukur kinerja perusahaan, dan menjadi alat komunikasi informasi atas operasi keberlanjutan yang telah dilakukan oleh perusahaan (Kuswanto, 2019).…”
Section: Kajian Pustaka Laporan Keberlanjutanunclassified
See 1 more Smart Citation
“…Laporan ini dipandang sebagai upaya perusahaan untuk menyampaikan aktivitas perusahaan yang berkenaan dengan aspek ekonomi, lingkungan dan sosial perusahaan. Tidak hanya itu, laporan keberlanjutan juga membantu perusahaan untuk menetapkan tujuan perusahaan, mengukur kinerja perusahaan, dan menjadi alat komunikasi informasi atas operasi keberlanjutan yang telah dilakukan oleh perusahaan (Kuswanto, 2019).…”
Section: Kajian Pustaka Laporan Keberlanjutanunclassified
“…Tema global tersebut antara lain ekonomi, lingkungan, praktik ketenagakerjaan dan pekerjaan yang layak, hak asasi manusia, masyarakat, dan tanggung jawab produk. Penggunaan standar GRI dapat menjadikan laporan keberlanjutan yang disusun oleh perusahaan di berbagai belahan dunia memiliki tingkat kompatibilitas yang tinggi (Kuswanto, 2019).…”
Section: Standar Griunclassified
“…Several businesses started publishing CSR initiatives as sustainability reports based on the GRI G2 criteria in 2006. Because many nations worldwide follow the Global Reporting Initiative (GRI) principles, their implementation is thought to enable sustainability reports to be sufficiently compatible (Kuswanto, 2019). Completing all the standards on the GRI indicators presents challenges for many businesses, nevertheless.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Indices calculated directly by researchers have a greater potential to obtain results that are biased, multi-interpretation, and experience human error. Based on research conducted by Kuswanto entitled "Application of GRI Standards in Sustainability Reports in Indonesia: An Evaluation" it is shown that based on conformity aspects, GRI G4 sustainability indicators are less accepted in Integrated Reporting practices in Indonesia [22]. The low level of emergence and conformity in conformity analysis indicates that the GRI G4 indicator cannot be fully disclosed in the Indonesian context.…”
Section: Ways To Encourage Companies To Optimize the Function Of Inte...mentioning
confidence: 99%